Climate-smart solutions for Mali: Findings from implementing the Climate-Smart Agriculture Prioritization Framework - Sogoba, Bougouna; Andrieu, N.; Howland, Fanny C.; Samaké, Ouodiouma B.; Corner-Dolloff, Caitlin; Bonilla Findji, Osana; Zougmoré, Robert B. (2016)
This info note summarizes findings of a pilot project aiming to develop a participatory framework to prioritize CSA practices and interventions to guide CSA investments in Mali. It was undertaken by researchers from the Malian Association of Awareness to Sustainable Development (AMEDD) and the International Center Tropical Agriculture (CIAT) as part of the CGIAR Research Program on Climate Change, Agriculture, and Food Security (CCAFS). Implementation was led by the Agency of Environment and Sustainable Development (AEDD) on behalf of the National Science-Policy dialogue platforms on Climate Change, Agriculture and Food Security (CCASA). Supported by the West Africa Regional Program, this research is part of a multi-region Prioritization project funded by CCAFS Flagship 1 on Climate-Smart Agricultural Practices.